Engaging with theoretical diffraction in teacher education. Issue 4 (4th July 2017) - Lanas, Maija; Rautio, Pauliina; Koskela, Anne; Kinnunen, Susanna; Viljamaa, Elina; Juutinen, Jaana
ABSTRACT: This article presents a study in which we began with a question 'how to teach theoretical reflectivity in teacher education', and ended with a sentence 'there is theoretical diffraction in teacher education'. The research presented in this paper took place in the context of a university course in which we have been involved for the past two years. During the course we simultaneously aimed to teach theoretical reflection and to analyse what was happening as we taught theoretical reflection. For two years we asked: What are students doing while we are trying to engage them in theoretical reflection? We noted that students are engaged in theory, but not in ways easily readable to the educators, and that the process could be called theoretical diffraction rather than reflection. Theoretical diffraction during the course was patterned by existing discursive practices: (1) disciplining emotions and focusing on control and answers; (2) personalising school as the teacher, and personally defending it; and (3) prioritising practice over theory and seeing both as dogma.